Hambatan Guru Pembimbing Khusus Terhadap Anak Berkebutuhan Khusus di Sekolah Inklusi SDN Keleyan 1 - Erni Erdita; Nova Estu Harsiwi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Inclusive education is an approach within the educational system that seeks to integrate all students, including those with special needs, into regular classrooms. The purpose of this study was to describe the obstacles experienced by special supervising teachers for children with special needs (ABK) at the inclusive school SDN Keleyan 1 Bangkalan. This research is a qualitative descriptive research with interview and observation data collection techniques. The subject of this study was one of the Special Needs Specialist teachers at SDN Keleyan 1 Bangkalan. The research results obtained were that there were 2 obstacles experienced by special supervising teachers. The first obstacle is related to inclusive school facilities and infrastructure, and the second obstacle is the distribution of material questions for children with special needs in each class. From these obstacles there are several factors that influence the occurrence of things like this, and there are also solutions that will be given. In